Energy metabolism of cerebral mitochondria during aging, ischemia and post-ischemic recovery assessed by functional proteomics of enzymes - Villa, Roberto Federico; Gorini, Antonella; Ferrari, Federica; Hoyer, Siegfried (Neurochemistry international, 2013)
Stroke is a leading cause of death and disability, but most of the therapeutic approaches failed in clinical trials. The energy metabolism alterations, due to marked ATP decline, are strongly related to stroke and, at present, their physiopathological roles are not fully understood. Thus, the aim of this study was to evaluate the effects of aging on ischemia-induced changes in energy mitochondrial transduction and the consequences on overall brain energy metabolism in an in vivo experimental model of complete cerebral ischemia of 15min duration and during post-ischemic recirculation after 1, 24, 48, 72 and 96h, in 1year “adult” and 2year-old “aged” rats. The maximum rate (Vmax) of citrate synthase, malate dehydrogenase, succinate dehydrogenase for Krebs’ cycle; NADH-cytochrome c reductase and cytochrome oxidase for electron transfer chain (ETC) were assayed in non-synaptic “free” mitochondria and in two populations of intra-synaptic mitochondria, i.e., “light” and “heavy” mitochondria. The catalytic activities of enzymes markedly differ according to: (a) mitochondrial type (non-synaptic, intra-synaptic), (b) age, (c) acute effects of ischemia and (d) post-ischemic recirculation at different times. Enzyme activities changes are injury maturation events and strictly reflect the bioenergetic state of the tissue in each specific experimental condition respect to the energy demand, as shown by the comparative evaluation of the energy-linked metabolites and substrates content. Remarkably, recovery of mitochondrial function was more difficult for intra-synaptic mitochondria in “aged” rats, but enzyme activities of energy metabolism tended to normalize in all mitochondrial populations after 96h of recirculation. This observation is relevant for Therapy, indicating that mitochondrial enzymes may be important metabolic factors for the responsiveness of ischemic penumbra towards the restore of cerebral functions.